Practical tips in bronchiectasis for Primary Care - Miguel Angel Martinez-Garcia; Alberto Garcia-Ortega; Grace Oscullo (npj Primary Care Respiratory Medicine, 2022)
Abstract Bronchiectasis is the third most common chronic inflammatory airway disease, after chronic obstructive pulmonary disease (COPD) and asthma with a prevalence clearly underestimated probably because of its clinical similitudes with other chronic airway diseases. Bronchiectasis can be caused by a dozen of pulmonary and extra-pulmonary diseases and a variable number and severity of exacerbations can appear throughout its natural history, usually with an infectious profile. The dilation of the airway and the inflammation/infection is their radiological and pathophysiological hallmarks. Primary Care should play an important play in many aspects of the bronchiectasis assessment. In this article, we will try to offer a series of important concepts and practical tips on some key aspects of the diagnosis and management of bronchiectasis in Primary Care: clinical suspicion, diagnostic methods, severity assessment, overlap with asthma and COPD and microbiological and therapeutic aspects.